tRNA-Derived Small RNAs and Their Potential Roles in Cardiac Hypertrophy - Cao, Jun; Cowan, Douglas B.; Wang, Da-Zhi (Frontiers in Pharmacology, 2020)
Transfer RNAs (tRNAs) are abundantly expressed, small non-coding RNAs that have long been recognized as essential components of the protein translation machinery. The tRNA-derived small RNAs (tsRNAs), including tRNA halves (tiRNAs) and tRNA fragments (tRFs), were unexpectedly discovered and have been implicated in a variety of important biological functions such as cell proliferation, cell differentiation, and apoptosis. Mechanistically, tsRNAs regulate mRNA destabilization and translation, as well as retro-element reverse transcriptional and post-transcriptional processes. Emerging evidence has shown that tsRNAs are expressed in the heart, and their expression can be induced by pathological stress, such as hypertrophy. Interestingly, cardiac pathophysiological conditions, such as oxidative stress, aging, and metabolic disorders can be viewed as inducers of tsRNA biogenesis, which further highlights the potential involvement of tsRNAs in these conditions. There is increasing enthusiasm for investigating the molecular and biological functions of tsRNAs in the heart and their role in cardiovascular disease. It is anticipated that this new class of small non-coding RNAs will offer new perspectives in understanding disease mechanisms and may provide new therapeutic targets to treat cardiovascular disease.